Linking creating shared value to customer behaviors in the food service context. (June 2020) - Ham, Sunny; Lee, Seoki; Yoon, Hyejin; Kim, Changsik
Abstract: Porter and Kramer proposed creating shared value (CSV) as the next phase after corporate social responsibility (CSR). Unlike CSR, CSV aims to create social value through business functions. By implementing CSV, a company can make a positive impact on society while creating economic value for itself simultaneously. The current study examines the effect of the two CSV dimensions, economic and social contributions, on consumers' brand attitude in the food service context. Further, it examines consumers' perceptions of a company's integration of the two dimensions as a potential moderator based on congruity theory.